2009
DOI: 10.1007/s11250-009-9304-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii in sheep and goats in Rahim Yar Khan (Punjab), Pakistan

Abstract: Toxoplasmosis, an infection caused by Toxoplasma (T.) gondii Apicomplexa protozoan, is widespread in humans and other animal species, having already been reported in many countries and different climates. In Pakistan, no data is available on this aspect among food animals. This study was undertaken to determine the seroprevalence of T. gondii infection in sheep and goats. A total of 200 serum samples from sheep and goats, were collected from urban area of Rahim Yar Khan (Punjab), Pakistan and tested for Toxopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
31
6
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 27 publications
20
31
6
1
Order By: Relevance
“…This result differs from those reported by Ramzan et al (2009) and Van Der Puije et al (2000), who observed that females were more affected than males, which was probably due to the lower immunologic resistance of females in some periods of their lives.…”
Section: Discussioncontrasting
confidence: 99%
“…This result differs from those reported by Ramzan et al (2009) and Van Der Puije et al (2000), who observed that females were more affected than males, which was probably due to the lower immunologic resistance of females in some periods of their lives.…”
Section: Discussioncontrasting
confidence: 99%
“…The toxoplasma prevalence rates found in this study were higher in sheep than goats (31.01% vs. 17.11%). This finding was disagreed with the results reported by Ahmed et al (2008) and Ramzan et al (2009) who concluded that goats are more susceptible to toxoplasmosis than sheep due to their higher activity and movement. These activities increase the probability of contact with contaminated sources.…”
Section: Discussioncontrasting
confidence: 92%
“…This finding supports the results reported by several researchers in different parts of the world (Kozojed et al 1976;Ahmed et al 2008;Barakat et al 2009;Ramzan et al 2009) who concluded that goats are more susceptible to toxoplasmosis than sheep as a result of their higher activity and movement compared with sheep, which increases the probability of contact with contaminated sources.…”
Section: Discussionsupporting
confidence: 91%